A Study of Distribution Patterns and Densities of Villages in Suphan Buri Province Classified According to Toponyms - Phansomboon, Tawan; Jirasirichote, Arisa (Journal of Arts and Thai Studies, 2024)
Objectives: Suphan Buri province, located in the central region of Thailand, is characterized by diverse landscapes and rich cultural heritage. The province is home to significant water resources, making it highly suitable for agricultural activities, which serve as a vital and predominant component of its economy. Combined with many transportation routes, these factors make this province have an attraction for human settlement. This research aimed to classify the villages in Suphan Buri based on their topographic characteristics, analyze the spatial distribution patterns of villages in relation to these characteristics, and assess village density across different topographic zones. Methods: Village data of Suphan Buri in 2023 was obtained from the Suphan Buri Provincial Administrative Office. Village names were classified according to three main types of toponyms: toponyms that relate to only one aspect of geography, toponyms that relate to more than one aspect of geography, and other toponyms, including the classification of 27 subtypes of toponyms and considering the frequency of the most common place names in Suphan Buri by analysing only the main words and secondary words that are nouns in the village names. Verbs and adverbs were ignored. Then, the distribution pattern of villages was interpreted according to toponyms using the Nearest Neighbor Index (NNI), and the village density analyzed according to toponyms using the Kernel Density Estimation technique. Results: The study’s results found that there is a total of 1,008 villages in Suphan Buri province. Most toponyms were related to only their geographical locations, 528 villages (52.38 percent), and the characteristic of toponyms was mostly related to the geographical features. The village names most frequently contained the word “Nong”. For the distribution of villages, it was found that the lowest NNI value (cluster) was found in the toponym, topography + plant, while the highest NNI value(disperse) was found in the toponym, plant + name of an important person. The density of villages in Suphan Buri was found to be very dense in Mueang Suphanburi district, Bang Pla Ma district, U Thong district, Song Phi Nong district, Si Prachan district, Sam Chuk district, and Doem Bang Nang Buat district, which are less than 100 meters in height and are in agricultural areas, including being next to the Suphan Buri River and the Chorakhe Sam Phan River. Application of this study: Relevant agencies can publish this information on their websites so that the general public can know the history and realize the value of each locality. The results can be applied to expand tourism that is in line with the local community, organize travel routes, and be used as a guideline for local development that will benefit the public in the future.